METAKONDISI PENGURUS DKM DI KOTA BOGOR: - M Taufik Hidayatulloh (Jurnal Dialog, 2017)
This study aimed at describing the personal characteristics, motivation, and performance of mosque committee members (Dewan Kemakmuran Masjid). In addition, this study also attempted to describe the leadership and the managerial competence of the mosque committee chairmen. This study was conducted from May to November 2015 in Bogor regency with 215 respondents as the sample. The number of samples in each district was determined by using proportionate stratified random sampling technique. Data were analyzed by using descriptive statistical analysis. The results showed that in general, the DKM members are in the productive age with high level of learning orientation. Their motivation can be classified as moderate to high, particularly on the motivation to affiliate. However, the performance of the DKM members as a whole tends to be low, with the highest performance in the program implementation. On the other hand, the leadership of DKM chairmen is categorized as middle to high, with the highest score in the ability to relate to others. Additionally, their managerial competence in general is in the moderate to high category, particularly in the internal cooperation.